Effect of swirling flow on Fluidised bed drying of piper Nigrum: an experimental study - Nur Fatihah, Mohd Roslan (2022)
Piper nigrum (Black pepper) is one of the well-known spices used worldwide, especially in India and Southeast Asia. Piper nigrum is a drupe with a diameter of about 5 mm (0.2 inch). Its odour is pungent, penetrating, and aromatic, and its taste is hot, bitter, and spicy. Piper nigrum is processed from unripe, raw green berries from the pepper plant, after which the drying process is applied to remove the moisture. Drying is one of the most popular methods of preserving a wide variety of agricultural products. One of the conventional processes in drying the piper nigrum is by using sun drying. Unfortunately, sun drying operation may negatively influence product hygiene because of contamination of dust, dirt, and insects. Thus, new drying techniques are continuously being sought. Fluidised bed dryers are widely used to dry wet materials due to the advantages of good mixing efficiency as well as high heat and mass transfer rate. But another reason for poor drying efficiency is a lack of design on the distributor plate. This study aims to investigate drying of piper nigrum using conventional sun drying method and swirling fluidised bed drying. The drying characteristic of piper nigrum using a swirling fluidised bed dryer is investigate by varying different designs of fluidised bed dryer’s air distributor, namely perforated, 45° and 67° inclination angles of air distributors. In addition, to study the effect of different distributor designs on the hydrodynamics of piper nigrum in a swirling fluidised bed. The drying experiments are conducted using three different temperatures: room temperature, 40 °C, and 50 °C. The effectiveness of the swirling fluidised bed dryer is accessed using the percentage of moisture content reduction. The effect of distributor design on hydrodynamics performance of piper nigrum in a fluidised bed dryer was investigated using five different weights (250 g, 500 g, 750 g, 1000 g and 1250 g). Drying using swirling fluidised bed dryer recorded 9 hours saves drying time about 66.7% as compared to conventional drying recorded at 27 hours. In this study, the drying rate of piper nigrum using a swirling fluidised bed dryer operated with a 45° inclination angle distributor records 9.7% higher than the 67° inclination angle distributor and 1.6% higher than operated with perforated distributor based on the weight after drying. From the hydrodynamics experiment, the distributor that contributed to lower pressure drops and improved particulate mixing in a swirling fluidised bed dryer was found to be 67° inclination angle distributor with 85.2 mmH2O at 1000 g of piper nigrum and reaching uniform minimum fluidisation at 0.23 m/s. Thus, 1000 g of piper nigrum is a suitable weight to operate using swirling fluidised bed dryer in the hydrodynamics experiment. In conclusion, the best distributor performance that could give an advantage in drying using fluidised bed dryer was 45° inclination angle distributor and for hydrodynamics experiment was 67° inclination angle distributor.